DMD deletions underlining mild dystrophinopathies: literature review highlights phenotype-related mutation clusters and provides insights about genetic mechanisms and prognosis - Fortunato, Fernanda; Tonelli, Laura; Farnè, Marianna; Selvatici, Rita; Ferlini, Alessandra (Frontiers in Neurology, 2024)
DMD gene pathogenic variations cause a spectrum of phenotypes, ranging from the severe Duchenne muscular dystrophy, the Becker milder cases, the intermediate or very mild muscle phenotypes invariably characterized by high CK, and the ultrarare fully-asymptomatic cases. Beside these phenotypes, X-linked dilated cardiomyopathy is also caused by DMD mutations. Males carrying DMD deletions with absent or very mild phenotypes have been sparsely described. We performed a horizon scan on public datasets to enroll males with the above phenotypes and carrying DMD deletions to delineate myopathic genotype-phenotype relationships. We inventoried 81 males, which were divided into the following clinical categorization: fully-asymptomatic males aged >43 years (A, N=22); isolated hyperCKemia (CK, N=35); and mild weakness (any age) with or without high CK (WCK, N=24). In all cases, deleted intervals were exons 2 to 55, and no downstream exons were ever involved, apart from an exon 78 deletion in a WCK patient. All deletions were in-frame, apart from the known exception-to-the-rule of exon 2 and exon 78. We correlated the mild phenotypes (A and CK) to deleted exons, intronic breakpoints, exon-exon junctions, 3’ isoforms rule, and protein epitopes, and we found that some genetic profiles are exclusively/mainly occurring in A/CK phenotypes, suggesting they are compatible with a quasi-normal muscular performance. We discussed diverse pathogenic mechanisms that may contribute to mild dystrophinopathic phenotypes, and we tried to address some “critical” genetic configurations or exon content needed to preserve a semi-functional DMD gene.